Nanay Mameng - Arumpac, Adjani ([Place of production not identified Production company not identified], 2012)
Mother Mameng delves deep into the character of a woman who has experienced extreme poverty and domestic violence and rose from from it all to become the beloved personality, well-known to the Philippine mass movement.
Summary taken from: https://www.imdb.com/title/tt3809658/?ref_=fn_al_tt_1
DVD
In Tagalog
Keywords: Documentary films